Two new species of Rhagovelia (Hemiptera: Heteroptera: Veliidae) from Costa Rica, with a key and new records from the country - Moreira, Felipe Ferraz Figueiredo (2015)
Rhagovelia danpolhemi sp. nov., from the Caribbean Slope of Costa Rica and R. springerae sp. nov., from the northern portion of the country, are described, illustrated, compared with similar species, and included in a key to species recorded from the country. Rhagovelia calopa Drake & Harris, R. spinosa Gould, and R. tantilla Drake & Harris are recorded for the first time from Costa Rica. New provincial records are provided for R. acuminata Bacon, R. angustipes Uhler, R. armata (Burmeister), R. bisignata Bacon, R. crassipes Champion, R. elegans Uhler, R. femoralis Champion, R. solida Bacon, R. spinigera Champion, R. tenuipes Champion, and R. uncinata Champion. Additional distributional information is given for these species and for R. formosa Bacon and R. scabra Bacon.